A comparison of sonography and radiography student scores in a cadaver anatomy class before and after the implementation of synchronous distance education. (February 2015) - Bagley, Jennifer Elaine; Randall, K; Anderson, MP
Distance education is a solution to expand medical imaging education to students who might not otherwise be able to obtain the education. It can be a mechanism to reduce the health care worker shortage in underserved areas. In some cases, distance education may be a disruptive technology, and might lower student performance. This study compares student scores in a cadaver anatomy course in the four cohorts preceding the implementation of distance education to the first three cohorts that took the course using a multiple campus design. The means and medians of the lecture exam average, the laboratory component score, and the final course score of the nondistance education cohorts were compared with those of the distance education cohorts using nonparametric statistical analysis. Scores in an anatomy course were compared by campus placement among the distance education cohorts, and the independent effect of distance education on the laboratory component, lecture examination average, and final course scores, while controlling for cumulative grade point average and site (originating/distant), was assessed. Students receiving the course in a nondistance education environment scored higher in the anatomy course than the students who took the course in a distance education environment. Students on the distant campus scored lower than students on the originating site. Distance education technology creates new opportunities for learning, but can be a disruptive technology. Programs seeking to implement distance education into their curriculum should do so with knowledge of the advantages and disadvantages.